Study of Similarities of Terms in Title, Author's Keywords and Controlled Vocabulary for Determining the Appropriate Field in Scientometric Thematic Analysis - Farideh Osareh; Mohammad Tavakolizadeh-Ravari; Zahed Bigdeli; Roghayeh Ghazavi (مدیریت اطلاعات سلامت, 2018)
Introduction: One problem in conducting scientometric thematic analysis is selecting which of the bibliographic fields containing the topics can be analyzed. This study aimed to compare subject fields of documents to determine the field or a combination of fields which are suitable for conducting a complete and proper thematic analysis in scientometrics.